Permanent junctional reciprocating tachycardia in children: a multicentre study on clinical profile and outcome. Issue 1 (14th April 2005) - Vaksmann, G; D'Hoinne, C; Lucet, V; Guillaumont, S; Lupoglazoff, J-M; Chantepie, A; Denjoy, I; Villain, E; Marçon, F
Abstract : Objectives: To investigate the clinical profile, natural history, and optimal management of persistent or permanent junctional reciprocating tachycardia (PJRT) in children. Methods and results: 85 patients meeting the ECG criteria for PJRT were enrolled in a retrospective multicentre study. Age at diagnosis varied from birth to 20 years (median 3 months). Follow up ranged from 0.1 to 26.0 (median 8.2) years. At the time of referral, 24 of 85 patients (28%) had congestive heart failure that was resolved with medical treatment in all patients. Eighty three patients received drug treatment initially. Amiodarone and verapamil were the most effective with a success rate of 84–94% alone or in association with digoxin. Radiofrequency ablation of the accessory pathway was performed in 18 patients. There was a trend for a relation between age at ablation and the result of the procedure, failures being more common in younger patients (three of six procedures in younger and 15 of 18 in older children were successful; p  =  0.14). Two patients with persistent left ventricular dysfunction on echocardiography but with no symptoms of congestive heart failure died suddenly one month and three years after diagnosis. PJRT resolved spontaneously in 19 patients (22%). Age at diagnosis of PJRT was not a predictor of spontaneous resolution. Conclusions: PJRT is a potentially lethal arrhythmia in children with tachycardia induced cardiomyopathy. Spontaneous resolution of tachycardia is not uncommon. Antiarrhythmic treatment is often effective. Radiofrequency ablation should be performed in older children or when rate is not controlled, especially in patients with persistent left ventricular dysfunction.